Understanding the Application of Emulsion Systems for Bacterial Encapsulation and Temperature-Modulated Release - Nur Suaidah Mohd Isa; Hani El Kadri; Daniele Vigolo; Nur Farra Adlina Mohamed Zakhari; Konstantinos Gkatzionis (Fluids)
The encapsulation of bacteria in emulsion droplets offers various advantages over other conventional methods of encapsulation, such as improvements in bacterial viability, and may serve as microenvironments for bacterial growth. Nevertheless, changes in temperature may affect bacterial viability and droplet stability. In this study, the encapsulation of bacteria in single water-in-oil (W/O) and double water-in-oil-in-water (W1/O/W2) emulsions under cold storage and temperature-modulated release were investigated. The microencapsulation of bacteria in emulsion droplets was achieved by using a flow-focusing microfluidic device. Droplet stability was determined by measuring changes in droplet size and creaming behaviour at different temperatures. The thermal properties of the samples were determined by using differential scanning calorimetry, while the release of bacteria with changes in temperature was determined by measuring the colony form unit (CFU) of the released bacteria and conducting fluorescence microscopy. Higher bacterial viability was observed for encapsulated samples compared to free cells, indicating the ability of the emulsion system to improve bacterial viability during cold-temperature storage. The crystallisation temperature was lowered in the presence of bacteria, but the melting temperature was similar with or without bacteria. Storage in freezing temperatures of −20 °C and −80 °C led to extensive droplet destabilisation, with the immediate release of encapsulated bacteria upon thawing, where the temperature-modulated release of encapsulated bacteria was achieved. This study provides an overview of the potential application of emulsion droplets for bacterial encapsulation under cold-temperature storage and the controlled release of encapsulated bacteria mediated by changes in temperature, which is beneficial for various applications in industries such as food and pharmaceuticals.